Angle-resolved femtosecond photoelectron spectroscopy of fullerenes - Johansson, Olof Johan (The University of Edinburgh, 2011)
An experimental apparatus has been constructed to investigate ionisation mechanisms of complex molecules and nanoparticles after femtosecond and/or picosecond laser excitation. The photoproducts are detected by time-of-flight mass spectrometry and velocity-map imaging (VMI) photoelectron spectroscopy. Test measurements on C60 and Xe have successfully reproduced previously published work indicating that the setup is working in a satisfactory manner. New detailed investigations of mass spectra and angle resolved photoelectron spectra (PES) have been carried out as a function of laser intensity, wavelength and pulse duration for C60 and C70, providing new insights into the electronic structure and ionisation mechanisms of these molecules. For 400 nm, 130 fs laser excitation, an isotropic contribution from thermally emitted electrons is found. A series of peaks are seen superimposed on the thermal background with binding energies in agreement with the recently discovered superatom molecular orbitals (SAMOs) of C60 [Feng et.al. Science 320 (2008) p. 359]. Furthermore, the angular dependence of the peak in the PES corresponding to the s-SAMO is in agreement with this assignment. To confirm the assignment of the other observed peaks it is concluded that the measured photoelectron angular distributions (PADs) need to be compared to calculated angular distributions. Measurements have also been made with the same wavelength but with a pulse duration of about 5 ps. Mass spectra, PES and PADs for these measurements show that the main ionisation mechanism for these laser conditions is delayed (thermionic) ionisation. For 800 nm, 130 and 180 fs laser excitation, thermally emitted electrons are observed. In contrast to the 400 nm measurements, the PADs show an asymmetry with higher apparent temperatures along the laser polarisation direction. Measurements were also made for longer pulse durations (1.0 – 3.8 ps). For pulse durations above 1 ps the asymmetry is gradually reduced while the delayed ionisation component in the mass spectrum increases with increasing pulse duration. The asymmetry is compared to calculations made assuming a field-assisted thermal electron emission. Similarly to the 400 nm experiments, a series of peaks are seen superimposed on the thermal background. PADs are presented for these peaks. PADs for peaks with the same binding energy as peaks seen in the 400 nm experiments follow the same trend. Isotropic PADs after ns laser excitation are also presented confirming delayed ionisation for these pulse durations.
Keywords: physical chemistry; fullerenes; photoelectron spectroscopy; ultrafast spectroscopy